EFEK PEMBERIAN VITAMIN E TERHADAP PENURUNAN KADAR MALONDIALDEHID (MDA) HATI MENCIT STRAIN JEPANG AKIBAT PAPARAN MINYAK GORENG BERULANG - Sy, Elmatris; Alioes, Yustini; -, Almurdi (Universitas Andalas, 2010)
ABSTRACT SOR (Reactive Oxygen Species) is a collection of free radical compound or compounds that easily become free radicals and can damage the cell membrane is marked by elevated levels of MDA (11) This is called oxidative stress, which can be prevented and reduced by adequate intake of antioxidants into the body optimally. Oxidative stress effects can be prevented by antioxidant vitamins, especially vitamin E. The results of research show that the average value of mouse liver MDA levels of the control group (A) 1.78 nmol/mL. The treatment group with repeated delivery of cooking oil (B) have increased the average value of mouse liver MDA levels (2.97 nmol/mL, 3.18 nmol/mL, 3.49 nmol/mL, 3.83 nmol/mL). In the treatment group with doses of vitamin E 52 IU/Kg/Hr and repeat cooking oil (C) have decreased the average value of mouse liver MDA levels (2.03 nmol/mL, 2.10 nmol/mL, 2.24 nmol/mL, 2.70 nmol/mL), compared with the provision of cooking oil over it. We can conclude that there are differences in average MDA levels of the liver of mice a significant between group A, group B1, C1 group (p = 0.003). Mice liver MDA content significantly between group A, group B2, C2 group (p = 0.000), between group A, group B3, C3 group (0.001), between group A, group B4, C4 group (0.000) where p <0.05. Keywords: Recurring Cooking Oil, Vitamin E, Malondialdehid (MDA)